BREAKDOWN VOLTAGE OF MICRON RANGE AIR INCLUSIONS IN CAPACITOR PAPER - O. O. Palchykov (National Technical University "Kharkiv Polytechnic Institute", 2020)
Purpose. To substantiate the breakdown mechanism of capacitor paper on the basis of numerical-field models with segmented cross-sections of cylindrical volumes of air and water, and also use the proposed models to determine the breakdown strength of air in micron-sized gaps under normal conditions. Methodology. The model bases on a finite element solution to an electrostatic problem in a volume of capacitor paper consisting of cellulose and pores with air and water. First, the possible scenarios for the growth of breakdown in capacitor paper are analyzed and to the conclusion is made, that complete breakdown developed from a partial breakdown in the air cavity. A brand of capacitor paper is chosen in such a way that when its thickness changed, the breakdown strength of the electric field changed over a wide range. Then, for the paper with the lowest average electric field intensity the possibility of explaining the complete breakdown by the breakdown of air segments on the basis of the Paschen dependence is checked. Further points of the obtained dependence by constructing models of papers of the same brand and a different thickness under the assumption of the similarity of electrostatic fields are determined. As such a criterion, the constancy of the equivalent effective permittivity are taken. Results. The dependence of the breakdown strength of the air in the range of 1.36...5.54 μm under normal conditions is determined. The obtained relationship is between the Peschot and Taev curves. Originality. For the first time, the possibility of indirectly estimation the breakdown strength of an insulating material using an electrostatic field model is indicated. Practical value. The proposed method for the numerical calculation of the breakdown voltage of air inclusions in the presence of water inclusions in the thickness of solid insulation can be applied to other types of solid thin-layer insulation.